2018
DOI: 10.1016/j.ceramint.2017.12.145
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption properties of CoGd substituted ZnFe2O4 ferrites synthesized by co-precipitation technique

Abstract: A series of co-precipitated Zn1-xCoxGdyFe2-yO4 spinel ferrites (x=0.0-0.5, y=0.00-0.10) sintered at 1000 o C were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), vibrating sample magnetometery (VSM) and microwave cavity perturbation (MCP). XRD patterns and FTIR spectra reveal formation of the spinel phase along with few traces of GdFeO3 second phase. The lattice constant decreases with an increasing amount of CoGd ions due to the seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Figure 6a,b presents changes in the value of real and imaginary part of permittivity with increasing temperature. Permittivity of ferrites in high frequencies is depending on the electronic and atomic polarization of grains and polarization of defects 58 . The nearly constant values of ε′ in wide frequency range can be associated with the fact that the interfacial and dipolar polarizations play important role at lower frequencies (according to the Koop’s theory), whereas in higher frequencies, especially in GHz region, changes (observed for (Zn,Mg,Ni,Fe,Cd)Fe 2 O 4 HEF) can be associated with polarization of defects.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6a,b presents changes in the value of real and imaginary part of permittivity with increasing temperature. Permittivity of ferrites in high frequencies is depending on the electronic and atomic polarization of grains and polarization of defects 58 . The nearly constant values of ε′ in wide frequency range can be associated with the fact that the interfacial and dipolar polarizations play important role at lower frequencies (according to the Koop’s theory), whereas in higher frequencies, especially in GHz region, changes (observed for (Zn,Mg,Ni,Fe,Cd)Fe 2 O 4 HEF) can be associated with polarization of defects.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra are presented in figure 7 in a range of 400-800 cm −1 . The two observed essential bands of the M-O bond phonon modes, ν IV in the range 560-580 cm −1 corresponding the tetrahedral site and ν VI in the range 395-450 cm −1 corresponding octahedral site, are the common FTIR bands observed for spinel ferrites [37]. Unlike the octahedral band frequency ν VI , the tetrahedral one ν IV decreases with increasing Mg content.…”
Section: Ftir Spectramentioning
confidence: 85%
“…Some studies have shown the effects of rare-earth elements on static magnetic properties and EM wave absorbing properties of M-type ferrite in recent years. , The unique magnetic property could attribute to the absorption of the EM wave . However, the higher density of the ferrite still impedes the applications of the rare earth-based composites . Light weight still remains a challenge to the advanced absorbing materials .…”
Section: Introductionmentioning
confidence: 99%